SMART MITIGATION LEARNING : INOVASI PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BUMISANA (BUKU SAKU MITIGASI BENCANA) BERBANTUAN AUGMENTED REALITY (AR) UNTUK MENINGKATKAN DISASTER LITERACY AWARENESS SISWA SEKOLAH DASAR DI JAKARTA - Indah Wardatussa'idah; Taofik; Rahmawati; Anggit Aruwiyantoko; Chrisnaji Banindra Yudha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Jakarta is one of the regions in Indonesia with a high vulnerability to various natural disasters. Conversely, the level of disaster literacy awareness among elementary school students remains relatively low due to the limitations of interactive and contextual learning media. This study aims to develop and test the feasibility of